Cowpea seed nutrients: Impacts on nutritional quality and acceptability of bread (Bangladesh Journal of Scientific and Industrial Research, 2024)
White bread is a fermented, energy-dense food with minimal protein and certain macro and micronutrients required for important living functions. In this study, bread was fortified with roasted cowpea flour (RCF) in varied amounts (0-20%). The chemical compositions and sensory properties of RCF-supplemented bread samples were evaluated using conventional procedures. Proximate analysis results demonstrated that RCF addition greatly raised the crude fiber (1.78-2.32%), ash (3.08-3.46%), fat (4.58-5.35%), and crude protein (13.81-16.82%) of the bread samples, while carbohydrate content (71.3-66.84%) reduced significantly. Supplementing bread with RCF increased the mineral content (calcium, iron, phosphorus, and magnesium) of the final bread samples. The sensory assessment score demonstrated differences in general acceptability between sample B (5% RCF with 95% wheat flour) and the other bread samples. Thus, supplementing white bread with RCF resulted in bread with improved nutritional content, particularly protein, magnesium, and phosphorous, which are required for good health.Bangladesh J. Sci. Ind. Res. 59(1), 27-34, 2024